Transfer and Success in the Acquisition of Verbal Properties in French and English - Sheppard, Ken (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1991)
AbstractThis study compares the acquisitional states of two groups of foreign language learners (a Francophone group learning English and an Anglophone group learning French) with a view to establishing the influence of Universal Grammar in the process. Specifically, the two groups (48 each) were asked to render acceptability judgments about 50 sentences in each language; the sentences exemplified syntactic properties [the permissability or impermissibility of fully tensed clausal complements, Exceptional Case Marking and Control structures (PRO)] associated with three verbs in the two languages (believe/croire, promise/promettre and want/vouloir).